Cytotoxicity of chlorhexidine digluconate to murine macrophages and its effect on hydrogen peroxide and nitric oxide induction - Bonacorsi, C. [UNESP]; Raddi, M.S.G. [UNESP]; Carlos, I.Z. [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2004)
Chlorhexidine, even at low concentrations, is toxic for a variety of eukaryotic cells; however, its effects on host immune cells are not well known. We evaluated in vitro chlorhexidine-induced cytotoxicity and its effects on reactive oxygen/nitrogen intermediate induction by murine peritoneal macrophages. Thioglycollate-induced cells were obtained from Swiss mice by peritoneal lavage with 5 ml of 10 mM phosphate-buffered saline, washed twice and resuspended (10(6) cells/ml) in appropriate medium for each test. Cell preparations contained more than 95% macrophages. The cytotoxicity was determined by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-tetrazolium bromide assay and the presence of hydrogen peroxide (H2O2) and nitric oxide (NO) by the horseradish peroxidase-dependent oxidation of phenol red and Griess reaction, respectively. The midpoint cytotoxicity values for 1- and 24-h exposures were 61.12 ± 2.46 and 21.22 ± 2.44 µg/ml, respectively. Chlorhexidine did not induce synthesis or liberation of reactive oxygen/nitrogen intermediates. When macrophages were treated with various sub-toxic doses for 1 h (1, 5, 10, and 20 µg/ml) and 24 h (0.5, 1, and 5 µg/ml) and stimulated with 200 nM phorbol myristate acetate (PMA) solution, the H2O2 production was not altered; however, the NO production induced by 10 µg/ml lipopolysaccharide (LPS) solution varied from 14.47 ± 1.46 to 22.35 ± 1.94 µmol/l and 13.50 ± 1.42 to 20.44 ± 1.40 µmol/l (N = 5). The results showed that chlorhexidine has no immunostimulating activity and sub-toxic concentrations did not affect the response of macrophages to the soluble stimulus PMA but can interfere with the receptor-dependent stimulus LPS.
Keywords: Chlorhexidine; Cytotoxicity; Macrophages; Nitric oxide; Hydrogen peroxide